The new alienated people between the Crusader and atheism (Their curricula, means, and methods) Descriptive study - Mustafa, Attia Morsi; Al-Tantawi, Walid Ali (Journal of Islamic Sciences, 2022)
The study aimed at identifying the intellectual roots of the phenomenon of the new Westerners who belong to our countries and speak with our tongues, and to reveal the most dangerous approaches used for these in the service of the Crusade and atheism.It sheds light on their most prominent means and methods to achieve their goals by monitoring, extrapolating and describing models of these Westerners, their intellectual backgrounds and their outlined approaches. The study also identifies their methods used, as they are in reality, which can be generalized to all other members of this phenomenon.The most prominent findings of the study can be summarized as follows; the intellectual affiliation of the Westerners to atheistic Western philosophy, their apprenticeship in the orientalist thought hostile to God, His Messenger and his religion, their adoption of philosophical thought in belief and worship, and their being tools and mechanisms of atheism and Christianization. In the postulates and absolutes and what is known from the Islamic religion by necessity, in addition to their admiration for Western civilization and their complete denial of Islamic civilization and all its achievements as the most prominent of their methods.
Keywords: Westernization; renewal; orientalism; Christianization; atheism; methods; means